Across country dairy breeding strategies in sub-Saharan Africa - Opoola, O. (University of Edinburgh, 2018)
Genetic improvement of farmed livestock has had a major impact on productivity, resource use efficiency, and food security, in many temperate countries over the last 70 years. Being permanent, cumulative and usually highly cost effective, genetic improvement is also of huge potential value in countries mostly in need of improved food security, like those in sub-Saharan Africa. However, most smallholder dairy farmers in these countries have not benefited from animal genetic improvement because of inconsistent breeding strategies, poor breeding infrastructure, small herd sizes and lack of performance recording systems. As a consequence, genetic improvement initiatives have mostly relied on importation of exotic breeds. Although when done properly this may underpin dairy production, there is concern that imported stocks are not always suitable and ad-hoc importations may marginalise indigenous genetic resources. With recent improvements in data recording and implementation of organised breeding schemes, together with recent advances in statistical genetics, there is an opportunity to develop new approaches to livestock improvement, suitable for application in sub-Saharan Africa. However, these new approaches need to be investigated and tested. Through the use of a scoping survey and analysis of dairy performance data of Holstein-Friesian and Jersey breeds from Kenya, South Africa and Zimbabwe, this thesis aimed to: (a) Examine the state of dairy improvement infrastructure with emphasis on the challenges and opportunities under different production systems. (b) Determine the commonalities in the source of sires used in dairy breeding among different countries. (c) Estimate genetic parameters based on the performance and pedigree information of cows within and across countries. (d) Determine the potential genetic gains that could be achieved from selection practiced within and across countries. Survey respondents identified challenges facing the different production systems and how they can be solved. Across the animal ancestry in seven generations for both studied breeds, family groups performing in the different countries could be traced back to common sires. Running genetic evaluations using pooled data from the three countries led to better genetic progress than using data from individual countries. Individual countries benefited at varying levels from the joint genetic evaluation of production and reproduction traits. A joint across-country genetic improvement programme has the potential to enhance future breeding strategies in sub-Saharan Africa.